RETINAL MANIFESTATIONS IN ADULT T-CELL LEUKEMIA/LYMPHOMA RELATED TO INFECTION BY THE HUMAN T-CELL LYMPHOTROPIC VIRUS TYPE-1. Issue 7 (July 2016) - Merle, Harold; Hage, Rabih; Meniane, Jean-Côme; Deligny, Christophe; Plumelle, Yves; Donnio, Angélique; Jean-Charles, Albert
Abstract : Purpose: To describe the retinal manifestations in adult T-cell leukemia (ATL) related to an infection by the human T-cell lymphotropic virus type-1 (HTLV-1). Methods: Retrospective case series of patients with ATL with retinal findings. Results: A total of 175 patients were diagnosed with ATL in Martinique between 1983 and 2013. Three of them showed intraocular findings related to ATL. They were bilateral deep retinal infiltrates associated with intermediate uveitis. In two cases, the ATL diagnosis was known. In the third, fluorescein angiography was remarkable for deep retinal infiltrates although fundus examination was unremarkable. The ATL cells were found in the blood of this patient. Despite chemotherapy, infiltrates progressed from the retinal periphery to the posterior pole in two patients, thus reducing visual acuity to light perception. They were associated with vasculitis. Conclusion: Retinal involvement in ATL is very rare. It can occur at any point during the natural course of the disease. Human T-cell lymphotropic virus type-1 carriers should benefit from a regular ophthalmic examination, and a fluorescein angiography must be performed in all patients with human T-cell lymphotropic virus type-1 with vitreous cells. The presence of deep retinal infiltrates must raise suspicion for ATL in a patient with human T-cell lymphotropic virus type-1. Abstract : The authors report the retinal manifestations throughout the course of adult T-cell leukemia linked to infection by the human T-cell lymphotropic virus type-1. The presence of deep retinal infiltrates must raise suspicion for adult T-cell leukemia in an human T-cell lymphotropic virus type-1 patient.